PENGARUH SOCIO-SCIENTIFIC ISSUE (SSI) DALAM MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS X FASE E DI SMAN 1 KECAMATAN SITUJUAH LIMO NAGARI - Angraini, Luthfiyanna Dwifa; Hidayat, Opi Rahmah; Sitepu, Nurlaila (Pendidikan Biologi FKIP UMMY, 2025)
This research was motivated by the low biology learning outcomes of Grade X Phase E students at SMAN 1 Kecamatan Situjuah Limo Nagari. One alternative to improve students’ learning outcomes is the use of Socio-Scientific Issues (SSI) in the Discovery Learning model. This study aims to examine the effect of using Socio-Scientific Issues (SSI) in the Discovery Learning model on biology learning outcomes of Grade X Phase E students at SMAN 1 Kecamatan Situjuah Limo Nagari. This research employed a quasi-experimental method with a posttest only control group design. The population consisted of all Grade X Phase E students at SMAN 1 Kecamatan Situjuah Limo Nagari, comprising six (6) classes. The sampling technique used was purposive sampling. The research instrument was an objective test. Data were analyzed using the Mann-Whitney U test followed by the Z test, with the hypothesis accepted if Zcalculated > Ztable. The results of data analysis showed that the data were not normally distributed but had homogeneous variance. The Mann–Whitney test followed by the Z test produced Zcalculated = -5.62 and Z0.5-α = 1.64, indicating that Zcalculated = -5.62 < Z0.5–α = 1.64, thus H1 was rejected. The conclusion of this study is that there is no significant effect of using the Socio-Scientific Issues (SSI) in the Discovery Learning model on biology learning outcomes of Grade X Phase E students at SMAN 1 Kecamatan Situjuah Limo Nagari at the 95% confidence level.